A Dynamical Compact Model of Diffusive and Drift Memristors for Neuromorphic Computing (Adv. Electron. Mater. 8/2022). (23rd August 2022) - Zhuo, Ye; Midya, Rivu; Song, Wenhao; Wang, Zhongrui; Asapu, Shiva; Rao, Mingyi; Lin, Peng; Jiang, Hao; Xia, Qiangfei; Williams, R. Stanley; Yang, J. Joshua
Abstract : Neuromorphic Computing Different from memory applications where only the static ending states are used, neuromorphic computing with memristors utilizes their dynamical switching process itself, which calls for a comprehensive dynamical memristor model. Such a model shown here can reproduce the long‐term memory of drift memristors and the short‐term plasticity of diffusive memristors. It captures quasi‐static and dynamic characteristics of these devices, demonstrating a good agreement with the experimental data. More details can be found in article number 2100696 by J. Joshua Yang and co‐workers.